Blood flow measurement in cervical and intracranial arteries using quantitative magnetic resonance angiography and duplex sonography (bocaccia) – a prospective observational study - Skoloudik, David; Fiedler, Jiri; Reiser, Martin; Hrbac, Tomas; Fadrna, Tana; Langova, Katerina; Herzig, Roman (Ultrasound in medicine & biology, 2019)
Cerebral blood flow volume (BFV) is important factor for accurate diagnosis of neurovascular diseases and treatment indication. Study aims to assess correlations of BFV measurements in cervical and intracranial arteries between quantitative magnetic resonance angiography (qMRA) and duplex sonography. Consecutive patients with suspicion of cerebral vascular pathology were included in prospective study. All patients underwent qMRA and duplex sonography of the cervical and intracranial arteries with measurement of BFV in bilateral common (CCA), internal (ICA) and externa carotid arteries, vertebral arteries (VAs), middle, anterior and posterior cerebral arteries, posterior communicanting arteries and basilar artery (BA). DS was performed using two ultrasound machines by experienced sonographers. Two patients were examined twice. Correlations between BFV measurements were evaluated using Spearman's correlation coefficient and inter-class correlation coefficient (ICC). Totally 21 subjects (15 males, mean age 56.3±6.2 years) were included to the study. Duplex sonography inter-investigator correlation was excellent (ICC=0.972) as well as intra-investigator correlations of both qMRA and duplex sonography (ICC˃0.990). Mostly high correlations were recorded between qMRA and duplex sonography BFV measurements in particular cervical arteries but only low to moderate correlations were obtained for intracranial arteries. Mean differences between BFV measurements in CCA and its branches were 10.9±8.1%/15.0±11.9% when using qMRA/duplex sonography, in ICA siphon and its branches 13.5±11.8%/35.4±34.2% when using qMRA/duplex sonography, and in both VAs and BA 24.1±19.7%/44.9±44.0% when using qMRA/duplex sonography, resp. Duplex sonography and qMRA are highly reproducible methods for blood flow volume measurement in cervical and intracranial arteries in routine clinical practice. The study was registered at ClinicalTrials.gov. NCT03591523 and supported by the Ministry of Health of the Czech Republic grants No. 16-29148A, 16-30965A, 17-31016A.